1980
DOI: 10.1210/jcem-50-6-1131
|View full text |Cite
|
Sign up to set email alerts
|

Unchanged Arginine-Induced Stimulation of Insulin, Glucagon, Growth Hormone, and Prolactin after Pretreatment with Indomethacin in Normal Man*

Abstract: The arginine-induced release of insulin, glucagon, GH, and PRL was studied in eight normal male volunteers. Pretreatment with indomethacin (150 mg for 3 days) failed to modify the effect of arginine on the release of these hormones. As both indomethacin and acetylsalicylic acid are potent inhibitors of the endogenous prostaglandin synthesis, these results indicate that the effect of acetylsalicylic acid on insulin and glucagon secretion, as described by others, seems to be unrelated to the suppression of endog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1981
1981
2002
2002

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 23 publications
(25 reference statements)
1
3
0
Order By: Relevance
“…Blood glucose, plasma NEFA, C-peptide, insulin and glucagon were totally unaffected by the two doses of indomethacin, both in the basal state and during the differing rates of arginine infusion. This observation is in agreement with the results of a similar study performed in healthy volunteers [33] but are in sharp contrast with those of studies in vitro which showed that indomethacin abolishes arginine-induced glucagon secretion by isolated guinea-pig islets [18,21]. A possible explanation for this discrepancy between the studies in vivo and in vitro is the fact that plasma concentrations of indomethacin in the present study were in the range of 10 nmol/ml and about 90% of the drug in the circulation is bound to plasma albumin and thus biologically unavailable.…”
Section: Discussionsupporting
confidence: 93%
“…Blood glucose, plasma NEFA, C-peptide, insulin and glucagon were totally unaffected by the two doses of indomethacin, both in the basal state and during the differing rates of arginine infusion. This observation is in agreement with the results of a similar study performed in healthy volunteers [33] but are in sharp contrast with those of studies in vitro which showed that indomethacin abolishes arginine-induced glucagon secretion by isolated guinea-pig islets [18,21]. A possible explanation for this discrepancy between the studies in vivo and in vitro is the fact that plasma concentrations of indomethacin in the present study were in the range of 10 nmol/ml and about 90% of the drug in the circulation is bound to plasma albumin and thus biologically unavailable.…”
Section: Discussionsupporting
confidence: 93%
“…After a 15-minute baseline period, L-arginine (30 g; 1 g/min) was infused intravenously over 30 minutes (29). Venous blood samples were taken at Ϫ15, 0, 15, 30, 45, 60, 90, and 120 minute(s) for measurement of leptin, insulin, C-peptide, glucagon, FFAs, and glucose.…”
Section: Arginine Infusionmentioning
confidence: 99%
“…In healthy subjects a stimulatory action of ASA has been described for insulin secretion in response to intravenous glucose and arginine [5,6]. In contrast, other inhibitors of PG synthesis, such as indomethacin decrease [7,8] or fail to affect insulin secretion [9]. As to tissue sensitivity to insulin, it has recently been demonstrated that ASA, apart from enhancing insulin secretion, impairs glucose metabolism, whereas ibuprofen fails to alter glucose disposal [5].…”
mentioning
confidence: 99%